International handbook of computer security - Shim, Jai K; Qureshi, Anique A; Sligel, Joel G (Chicago Glenlake, 2001)
The international handbook of computer security is written primarily to help business executives and information systems computer professional.The book addresses a wide range of computers security issues.The major topics discussed are company security pol
Keywords: Computer security-Handbooks, manuals, etc